IMALOGICAL MEASURINGS OF «OTHER /АLIEN» IN A STUDENT ENVIRONMENT (ON MATERIALS OF EMPIRIC SECRET SERVICE) - Kuprii, Tetyana (Educological discourse, 2017)
The dialog of cultures, as a rule, begins with іmalogy, which «examines the problem of presentations and sources of forming of appearances of countries and people in regard to other. On the basis of dialog of cultures the theory of cognition develops «other». Cognition «stranger – other – conduces other» to self-knowledge, to national originality and simultaneously to sense of respect to other people and their cultures. Appearances of «other» cultures, countries, people is a theme, interesting thinkers and writers of different epoches. Naturally, that in course of time perception and study purchased «other» scientific character. Thus, іmalogy is perspective direction of humanitarian science, which requires researches. As well as dialog of cultures, іmalogy must bring in the contribution to creation of favourable appearance of «other» countries of modern youth, in development of good-neighbourlinesses and exception of negative. The question of forming of objective appearances of «other /аlien» is in-process examined at consciousness of modern Ukrainian student youth as іmalogical measuring of becoming of conscious citizen. Factors and factors of forming of аccentual of negative appearances of modern student of young people open up. The features of display of the social іmalogical measurings of personality are investigational in the basic spheres of its vital functions in the period of preparation at higher school. Interdependence is analysed on the basis of results of empiric research between political events and phenomena in Ukraine and forming in the environment of student young people of marker / оr marginal public constructions which generate іmalogical offenses.